Tahapan Penerimaan Diri Disabilitas Sensorik Netra Bukan Bawaan Lahir - Dani, Wulan Rahma; Ruby, Arcivid Chorynia (Universitas Muria Kudus, 2025)
Visual sensory disability is a term that refers to a person's condition who has problems or difficulties in seeing. Self-acceptance is the ability to accept everything about oneself. This study aims to analyze the stages of self-acceptance in non-congenital visual sensory disabilities. The research subjects were selected based on the criteria of informants with non-congenital visual sensory disabilities. The data collection method for this study used a phenomenological approach with observation and interview techniques. The data analysis method used was coding and triangulation source credibility testing. The results showed that each informant experienced different stages of self-acceptance. Informant A went through stages of denial, anger, bargaining, depression and finally reached acceptance. A had felt hopeless, isolated himself, and thought about ending his life, but support from his family helped him to accept the situation. Informant S went through all stages, from denial, anger, bargaining, depression, to acceptance. S showed a high spirit to recover even though he had damaged things and thought about committing suicide. Meanwhile, Informant M only went through three stages, namely denial, anger, and acceptance. Family support and sports activities really helped him to get motivation for the future, even though M felt tired and pessimistic. Disabilitas sensorik netra adalah istilah yang merujuk pada kondisi seseorang yang mengalami masalah atau kesulitan dalam penglihatan. Penerimaan diri adalah kemampuan untuk menerima segala sesuatu tentang diri sendiri. Penelitian ini bertujuan untuk menganalisis tahapan penerimaan diri pada disabilitas sensorik netra bukan bawaan lahir. Subjek penelitian dipilih berdasarkan kriteria informan dengan penyandang disabilitas sensorik netra bukan bawaan lahir. Metode pengumpulan data penelitian ini menggunakan pendekatan fenomenologi dengan teknik observasi dan wawancara. Metode analisis data yang digunakan adalah coding dan uji kredibilitas triangulasi sumber. Hasil penelitian menunjukkan bahwa setiap informan mengalami tahapan penerimaan diri yang berbeda-beda. Informan A melewati tahapan penyangkalan, kemarahan, tawar-menawar, depresi dan akhirnya mencapai penerimaan. A pernah merasa putus asa, mengisolasi diri,dan berpikir untuk mengakhiri hidup,tetapi dukungan dari keluarganya membantunya untuk menerima keadaan. Informan S mengalami semua tahapan,mulai dari penyangkalan, kemarahan, tawar-menawar, depresi, hingga penerimaan. S menunjukkan semangat yang tinggi untuk sembuh meskipun sempat merusak barang dan berpikir untuk bunuh diri. Sementara itu, Informan M hanya melalui tiga tahapan, yaitu penyangkalan, kemarahan, dan penerimaan. Dukungan keluarga dan aktivitas olahraga sangat membantunya untuk mendapatkan motivasi untuk masa depan, meskipun M sempat merasa lelah dan pesimis.